Analisis Semiotika Makna Motivasi pada Lirik Lagu “Teramini” Karya Ghea Indrawari - Salsah Anggraeni; Liliyana Liliyana; Fajar Muharam (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
The development of music in Indonesia has experienced growth and change from time to time, with unique and varied characteristics. As Indonesians, it is important for us to help preserve Indonesian music by supporting local musicians and appreciating their works. Music has an important role in culture and human life, not only as a means of entertainment and artistic expression, but also has a significant psychological and emotional impact on listeners. This research focuses on analyzing the motivational meaning of the lyrics of the song "Teramini" by Ghea Indrawari, which gained popularity through social media such as TikTok and Instagram. Using Ferdinand De Saussure's semiotic theory approach, this research explores the meaning of motivation by analyzing the signifiers and signifieds contained in the song lyrics. The qualitative descriptive method was used with data collection techniques in the form of text research, where the researcher interpreted the verses of the lyrics of the song "Teramini" without involving direct informants. The results of this research reveal the motivational meaning contained in the lyrics of the song "Teramini", connecting syntagmatic and paradigmatic elements to understand the message that Ghea Indrawari wants to convey through her work. The main aim of this research is to explore and interpret the hidden motivational meanings in the lyrics of the song "Teramini", while another aim is to fulfill the graduation requirements in working on the author's thesis or final project. Thus, this research contributes to a deeper understanding of music as a communication medium that influences and inspires its audience.